Regular monitoring of cytomegalovirus-specific cell-mediated immunity in intermediate-risk kidney transplant recipients: predictive value of the immediate post-transplant assessment. (March 2019) - Fernández-Ruiz, M.; Giménez, E.; Vinuesa, V.; Ruiz-Merlo, T.; Parra, P.; Amat, P.; Montejo, M.; Paez-Vega, A.; Cantisán, S.; Torre-Cisneros, J.; Fortún, J.; Andrés, A.; et al.
Abstract: Objective: Previous studies on monitoring of post-transplant cytomegalovirus (CMV)-specific cell-mediated immunity (CMI) are limited by single-centre designs and disparate risk categories. We aimed to assess the clinical value of a regular monitoring strategy in a large multicentre cohort of intermediate-risk kidney transplant (KT) recipients. Methods: We recruited 124 CMV-seropositive KT recipients with no T-cell-depleting induction pre-emptively managed at four Spanish institutions. CMV-specific interferon-γ-producing CD4 + and CD8 + T cells were counted through the first post-transplant year by intracellular cytokine staining after stimulation with pp65 and immediate early-1 peptides (mean of six measurements per patient). The primary outcome was the occurrence of any CMV event (asymptomatic infection and/or disease). Optimal cut-off values for CMV-specific T cells were calculated at baseline and day 15. Results: Twelve-month cumulative incidence of CMV infection and/or disease was 47.6%. Patients with pre-transplant CMV-specific CD8 + T-cell count <1.0 cells/μL had greater risk of CMV events (adjusted hazard ratio (aHR) 2.84; p 0.054). When the CMI assessment was performed in the immediate post-transplant period (day 15), the presence of <2.0 CD8 + T cells/μL (aHR 2.18; p 0.034) or <1.0 CD4 + T cells/μL (aHR 2.43; p 0.016) also predicted the subsequent development of a CMV event. In addition, lower counts of CMV-specific CD4 + (but not CD8 + ) T cells at days 60 and 180 were associated with a higher incidence of late-onset events. Conclusions: Monitoring for CMV-specific CMI in intermediate-risk KT recipients must be regular to reflect dynamic changes in overall immunosuppression and individual susceptibility. The early assessment at post-transplant day 15 remains particularly informative.